Vortex dynamics of a jet at the pressure node in a standing wave. (10th January 2020) - Worth, Nicholas A.; Mistry, Dhiren; Berk, Tim; Dawson, James R.
Abstract : Abstract : In this paper we investigate the vortex structure and dynamics formed in the near field of a turbulent axisymmetric jet subjected to transverse acoustic forcing. Full three-dimensional phase-averaged velocity measurements were obtained to elucidate the coherent structures formed when the jet is positioned at the pressure node of a plane standing wave oriented transversely to the streamwise flow direction, which creates a plane symmetry about the nodal line dissecting the jet exit. Due to the change in phase that occurs across the nodal line, it was found that axisymmetry is broken and the jet undergoes a periodic transverse flapping motion consistent with a sinuous mode. This was accompanied by a periodic train of interconnected vortex structures, resembling inverted hairpin (or horseshoe) vortices, formed as the shear layers rolled up in anti-phase either side of the jet, and propagated a few diameters downstream before breaking up. An inviscid vortex model employing inverted hairpin line vortices is shown to capture both the dynamics of the vortex structures and the fluctuating velocity fields. Overall, the jet response and resulting vortex dynamics observed represent a significant departure from the axisymmetric flow structures observed with conventional longitudinal forcing and more closely resemble the phenomenon of bifurcating jets.